2011
DOI: 10.1074/jbc.m111.253104
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of Protein Kinase Cδ/Extracellular Signal-regulated Kinase/Poly(ADP-ribose) Polymerase-1 (PARP-1) Signaling Pathway in Histamine-induced Up-regulation of Histamine H1 Receptor Gene Expression in HeLa Cells

Abstract: The histamine H 1 receptor (H1R) gene is up-regulated in patients with allergic rhinitis. However, the mechanism and reason underlying this up-regulation are still unknown. Recently, we reported that the H1R expression level is strongly correlated with the severity of allergic symptoms. Therefore, understanding the mechanism of this up-regulation will help to develop new anti-allergic drugs targeted for H1R gene expression. Here we studied the molecular mechanism of H1R up-regulation in HeLa cells that express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
62
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 60 publications
(66 citation statements)
references
References 59 publications
(62 reference statements)
3
62
0
1
Order By: Relevance
“…Rottlerin has been used to confirm the possible role of PKCδ isoform in several signaling pathways. Moreover, the results obtained with rottlerin were compatible with those obtained utilizing more selective approaches to inhibit PKCδ in a previous report (17). It was recently reported rottlerin also inhibited PKCθ (23).…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…Rottlerin has been used to confirm the possible role of PKCδ isoform in several signaling pathways. Moreover, the results obtained with rottlerin were compatible with those obtained utilizing more selective approaches to inhibit PKCδ in a previous report (17). It was recently reported rottlerin also inhibited PKCθ (23).…”
Section: Discussionsupporting
confidence: 79%
“…We showed that treatment with PMA significantly increased glucagon secretion from isolated islets and quercetin treatment suppressed the PMA-induced increase in glucagon secretion in α-cells. We reported that quercetin suppressed PMA-induced Tyr 311 phosphorylation of PKCδ in HeLa cells (17). In the present study, we showed that quercetin also suppressed PMA-induced Tyr 311 phosphorylation of PKCδ in isolated islets.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…Next, we investigated the effect of these antihistamines on H1R gene expression in HeLa cells. We previously found that the protein kinase Cδ (PKCδ) / extracellularregulated kinase / poly (ADP-ribose) polymerase-1 signaling pathway is involved in H1R gene expression in HeLa cells and that pretreatment with rottlerin, a selective PKCδ inhibitor, completely blocks this pathway (15). Pretreatment with 5 μM rottlerin significantly decreased basal H1R gene expression to 60% of the control level, indicating that there is constitutive H1R activation in HeLa cells (Fig.…”
mentioning
confidence: 99%
“…The mechanism of LT-mediated up-regulation of H1R is unknown, although histamine up-regulates the expression of H1R mRNA in HeLa cells through protein kinase C (PKC)-mediated H1R gene transcription (10). However it was reported that treatment of OVAsensitized mice with PKC inhibitors (GF109203X and rottlerin) before provocation diminished not only the CysLT production but also the effects of LT such as eosinophil infiltration and AHR (11), suggesting the involvement of PKC in the LT signaling pathway.…”
Section: Combination Of Leukotorienementioning
confidence: 99%